A habitat selection model for Javan deer (Rusa timorensis) in Wanagama I Forest, Yogyakarta - DANANG WAHYU PURNOMO (Smujo International, 2010)
Abstract. Purnomo DW. 2010. A Habitat selection model for Javan deer (Rusa timorensis) in Wanagama I Forest, Yogyakarta. Nusantara Bioscience 2: 84-89.  Wanagama I Forest is the natural breeding habitat of Javan deer (Rusa timorensis de Blainville, 1822). Habitat changes had affected Timor's resource selection and caused the deer to move from undisturbed areas to developed areas with agriculture and human settlements. We suspected that the degradation of natural habitat caused this shift. The research aimed to identify factors that might influence future habitat selection. Habitat selection was analyzed by comparing proportions of sites actually used to sites that we considered available to use. The results of a logistic regression of site categories showed there are three habitat variables that influence resource selection:  sum of tree species (expß=1.305), slope (expß=1.061), and distance to a water source (expß=1.002). The three variables influence the deer existing in a certain site of Wanagama Forest and arrange resource selection probability function (RSPF).